Assessment of Pellets from Three Forest Species: From Raw Material to End Use - Quiñones Reveles, Miguel Alfonso; Ruiz García, Víctor Manuel; Ramos Vargas, Sarai; Vargas Larreta, Benedicto; Masera Cerutti, Omar; Ngangyo Heya, Maginot; Carrillo Parra, Artemio (Molecular Diversity Preservation International, 2021)
This study aimed to evaluate and compare the relationship between chemical properties, energy efficiency, and emissions of wood and pellets from madroño Arbutus xalapensis Kunth, tázcate Juniperus deppeana Steud, and encino colorado Quercus sideroxyla Humb. & Bonpl. in two gasifiers (top-lit-up-draft (T-LUD) and electricity generation wood camp stove (EGWCS)) in order to determine the reduction of footprint carbon. In accordance with conventional methodologies, we determined the extracts and chemical components (lignin, cellulose, holocellulose), and the immediate analyses were carried out (volatile materials, fixed carbon, ash content and microanalysis of said ash), as well as the evaluation of emission factors (total suspended particulate matter (PM2.5), CO, CO2, CH4, black carbon (BC), elemental carbon (EC), and organic carbon (OC)). The results were statistically analyzed to compare each variable among species and gasifiers. The raw material analyzed showed how the pH ranged from 5.01 to 5.57, and the ash content ranged between 0.39 and 0.53%. The content values of Cu, Zn, Fe, Mg, and Ca ranged from 0.08 to 0.22, 0.18 to 0.19, 0.38 to 0.84, 1.75 to 1.90, and 3.62 to 3.74 mg kg−1, respectively. The extractive ranges from cyclohexane were 2.48–4.79%, acetone 2.42–4.08%, methanol 3.17–7.99%, and hot water 2.12–4.83%. The range of lignin was 18.08–28.60%. The cellulose content ranged from 43.30 to 53.90%, and holocellulose from 53.50 to 64.02%. The volatile material range was 81.2–87.42%, while fixed carbon was 11.30–17.48%; the higher heating value (HHV) of raw material and pellets presented the ranges 17.68–20.21 and 19.72–21.81 MJ kg−1, respectively. Thermal efficiency showed statistically significant differences (p Arbutus xalapensis being the species with the highest energy yield. The use of improved combustion devices, as well as that of selected raw material species, can reduce the impact of global warming by up to 33% on a cooking task compared to the three-stone burner.